Pengaruh Bimengsantik (Bijak Mengelola Sampah Plastik) Dalam Membentuk Karakter Tanggung Jawab Dan Peduli Pada Siswa - Ratnawati, Yuyun Dwi; Rosyidi, Zudan (Jurnal Pendidikan Karakter, 2025)
This research contributes to understanding the importance of concrete approaches such as BIMENGSANTIK in forming positive character in students. The implications of this research can stimulate the attention of schools to consider similar integration programs in the character education curriculum to create a generation that cares more about the environment. The purpose of this journal is to determine the influence of the BIMENGSANTIK (Wisely Managing Plastic Waste) program on the formation of responsible and caring character in students. The research method used is the phenomenological method which involves collecting data through observation and interviews with teachers in elementary schools. The research results show that the BIMENGSANTIC program has a significant influence in forming responsible and caring characters in students. In conclusion, after participating in this program, students showed increased awareness of the importance of managing plastic waste wisely and being responsible in protecting the environment. Apart from that, students also show a caring attitude towards the negative impact of plastic waste on the environment and health